f(x)=(12x2+2x)(x1)\displaystyle f(x)=\left(\frac12x^2+2x\right)\cdot(x-1)

Für diese Aufgabe benötigst Du folgendes Grundwissen: Produktregel

%%\begin{align}\text{Produktregel:}\phantom{=}&\left(\color{blue}{u(x)}\cdot \color{green}{v(x)}\right)' =\color{blue}{u'(x)}\cdot \color{green}{v(x)} + \color{blue}{u(x)}\cdot \color{green}{v'(x)}\end{align}%%
%%\begin{align}f(x) &= \color{blue}{\left(\frac12x^2+2x\right)} \cdot \color{green}{(x-1)} \\f'(x) &= \color{blue}{(x+2)} \cdot \color{green}{(x-1)}+ \color{blue}{\left(\frac12x^2+2x\right)} \cdot \color{green}{1} \\&=x^2-x+2x-2+\frac12x^2+2x \\&=\frac32x^2+3x-2\end{align}%%